Employing the Unemployed of Marienthal: Evaluation of a Guaranteed Job Program - Maximilian Kasy; Lukas Lehner (Institute of Labor Economics (IZA), 2023)
We evaluate a guaranteed job program launched in 2020 in Austria. Our evaluation is based on three approaches, pairwise matched randomization, a pre-registered synthetic control at the municipality level, and a comparison to individuals in control municipalities. This allows us to estimate direct effects, anticipation effects, and spillover effects. We find positive impacts of program participation on economic and non-economic well-being, but not on physical health or preferences. At the municipality level, we find a large reduction of long-term unemployment, and no negative employment spillovers. There are positive anticipation effects on subjective well-being, status, and social inclusion for future participants.
Keywords: I38; J08; J45; 330; job guarantee; pairwise matched randomization; synthetic control